Isolation of Cellulosic Material from Agro-wastes and their Derivatization (Dhaka University Journal of Science, 2015)
Isolation of cellulosic materials from agricultural wastes such as skin of various fruits have been carried out. Isolated cellulosic materials have been converted into their acetate and carboxymethyl cellulose derivatives. The derivatives have been characterized by titrimetric method, pH- titration and FT-IR spectroscopy. The characteristic features of these derivatives suggest the possibilities of their commercial utilization. Hence, this will reduce the environmental pollution and help to develop economy of the country. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21767 Dhaka Univ. J. Sci. 63(1): 43-46, 2015 (January)